Relevansi Pemikiran Pendidikan Al-Ṭaḥṭawῑ terhadap Politik Pendidikan Islam di Indonesia - Dedi Setiawan; Khodijah Khodijah; Dedi Arianto (Bulletin of Indonesian Islamic Studies, 2022)
One of the Islamic Education figures in the modern era is Rifa'ah Baḍāwῑ Rāfi' Al-Ṭaḥṭawῑ. He was considered successful in formulating educational innovations following the times. This paper aims to describe the concept of Al-Tahtawi's education and relate it to the Islamic education system in Indonesia. This paper uses a type of literature-qualitative research. Data collection was carried out using the appropriate written reference source documentation technique. Data analysis was carried out using descriptive, content, and comparative methods. The results of the study show that Al-Ṭaḥṭawῑ has developed educational reform in Egypt through innovations such as the distribution of education based on age levels, universal education, education for all groups, gender equality, democratic education, and dynamic education. The political concept of Islamic education in Indonesia is the synergy between the state, politics, and education which encourages the formation of education following the ideals of the Indonesian nation. Meanwhile, the relevance of Al-Ṭaḥṭawῑ's educational thinking to the politics of Islamic education in Indonesia is that there are similarities in objectives in the delivery of education. These were marked by the development of educational innovations, educational renewal following current issues, the democratization of education, and improving the quality of human resources capable of mastering science and technology